The Dominance of Arabic and English in the Linguistic Landscape of Southwest Aceh: Implications for Students’ Interest and Government Perceptions - Muhammady, Aan; Juliana, Rena; Harahap, Masriana; Rani, Samsuar A.; Muslim, Buhori; Sapar, Ahmad Arifin bin (Universitas Islam Negeri Jurai Siwo Lampung, 2026)
Background: The linguistic landscape reflects language visibility, identity, and social values within public space. In the West–South coastal region of Aceh, the presence of Arabic and English in public signage represents the interaction between religious identity and global influence. However, the representation of these languages raises questions about accuracy, policy support, and their influence on students’ academic interests, particularly in Arabic language studies. Understanding this relationship is important for strengthening language education and public language policy in Islamic educational contexts. Research Objectives: This study aims to examine the dominance of Arabic and English in the linguistic landscape of the West–South coastal region of Aceh and to analyze its impact on students’ interest in Arabic language study programs as well as on governmental perceptions of language use. Methodology: This research employed a qualitative sociolinguistic approach. Data were collected through photographic documentation of 75 public signage items in educational institutions, government offices, mosques, and commercial areas, along with in-depth interviews with government officials and 25 dayah students in West Aceh, Nagan Raya, and Southwest Aceh. Purposive sampling was applied. Data was analyzed through descriptive qualitative approach, and triangulation was used to ensure trusworthiness. Results: Arabic signage appears symbolically strong in religious and institutional contexts but often contains grammatical and orthographic inaccuracies. English dominates commercial signage and is associated with modernity and economic value. Limited Arabic usage is influenced by low public comprehension, weak regulation, and limited policy support. Unique Contribution: This study connects linguistic landscape analysis with student interest in Arabic language education within an Islamic regional context. Conclusion: The linguistic landscape influences language perception, motivation, and educational orientation. Recommendations: Some recommendations to support Arabic language learning include strengthening language policy, improving Arabic inscription quality, and integrating linguistic landscape awareness into education.